(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In the realm of modern medicine, the prevention of atherosclerosis has emerged as a vital focus area. Atherosclerosis, a condition characterized by the buildup of plaque in arterial walls, poses significant health risks, including heart attacks and strokes. To combat this widespread health concern, researchers have turned their attention to the use of modern antioxidant agents – potentially a groundbreaking solution. However, despite the importance of this task, scientific research in this direction remains limited, specifically in terms of utilizing combined forms of various antioxidants for angioprotection across different age groups. This article delves into the significance of searching for the optimal drug that hinders atherosclerosis development and explores its clinical mechanisms. The prevention of atherosclerosis remains an integral part of modern medicine’s mission to ensure better cardiovascular health worldwide. While modern antioxidant agents offer significant potential, their combined use for angioprotection across different age groups demands more scientific research. The importance of identifying an optimal drug to combat atherosclerosis cannot be overstated, and in-depth studies on clinical mechanisms will contribute greatly to this endeavor. By prioritizing research in this direction, we can strive towards a future where atherosclerosis is effectively prevented, reducing the burden on individuals and healthcare systems alike.